2020
DOI: 10.3390/rs12020309
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Traits Determine the Success of LiDAR-Based Crown Mapping in a Mixed Temperate Forest

Abstract: The ability to automatically delineate individual tree crowns using remote sensing data opens the possibility to collect detailed tree information over large geographic regions. While individual tree crown delineation (ITCD) methods have proven successful in conifer-dominated forests using Light Detection and Ranging (LiDAR) data, it remains unclear how well these methods can be applied in deciduous broadleaf-dominated forests. We applied five automated LiDAR-based ITCD methods across fifteen plots ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 94 publications
(122 reference statements)
3
37
0
Order By: Relevance
“…Across a boreal forest, Nevalainen et al 19 found the accuracy of individual tree identification from the UAV photogrammetric point clouds varying between 26% and 96%, depending on the characteristics of the different test sites. These results confirm that heterogeneous forest structures (such as the Oak and Mix plots in this study) are challenging targets for automated individual tree crown detection and delineation using remotely sensed data 21,23 . On the other hand, an accuracy of >90% in delineated tree crows from UAV-derived 3D point clouds data was reported by Sanchez et al 28 , which is likely due to the simpler structure of the study area (an almond tree plantation).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Across a boreal forest, Nevalainen et al 19 found the accuracy of individual tree identification from the UAV photogrammetric point clouds varying between 26% and 96%, depending on the characteristics of the different test sites. These results confirm that heterogeneous forest structures (such as the Oak and Mix plots in this study) are challenging targets for automated individual tree crown detection and delineation using remotely sensed data 21,23 . On the other hand, an accuracy of >90% in delineated tree crows from UAV-derived 3D point clouds data was reported by Sanchez et al 28 , which is likely due to the simpler structure of the study area (an almond tree plantation).…”
Section: Discussionsupporting
confidence: 83%
“…The validation/reference data consisted of manually delineated crowns, a common approach when high or very high resolution imagery is available 21,22,41 . Considering the very high spatial resolution of the UAV orthomosaics (10 cm), tree crowns were extracted by a manual delineation approach in…”
Section: Automatic Tree Crown Delineation: Accuracy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Automatically segmented crown polygons were imported into ArcGIS Pro 2.5 (ESRI, Redlands, CA, USA), where the overlap between automatically and manually segmented crowns was classified as either over-segmentation, under-segmentation, false positive or true positive, following Hastings et al [40]. As the mITCs from the calibration plots were used to parametrize the segmentation model, the accuracy assessment was also applied to the mITCs from the validation plots to allow for independent validation.…”
Section: Validation 271 Individual Tree Segmentation Accuracy Assementioning
confidence: 99%
“…Crown delineation is critical for remote sensing of individual trees, as well as improving broad scale studies of forest ecology, silviculture and ecosystem services [1]. There have been dozens of proposed crown delineation algorithms, but these algorithms are designed for and evaluated using a range of different data inputs [24], sensor resolutions [5], forest structures [6,7], and evaluation protocols [8,9]. This diversity of approaches makes it difficult to track algorithmic progress and prevents practitioners from weighing tradeoffs in proposed pipelines.…”
Section: Introductionmentioning
confidence: 99%